A framework for evaluating the sustainability and economic viability of crop-livestock systems in sub-Saharan Africa - Ehui, Simeon K.; Jabbar, M.A. (IAEA, 1997)
Improved crop-livestock production systems and technologies are currently being developed in sub-Saharan Africa in response to the growing demand for food and the degradation of the natural resource base. These technologies must not only enhance food production, but they also need to maintain ecological stability and preserve the natural resource base, that is, they must be sustainable. However, the notion of sustainability has been of limited operational use to policy-makers and researchers attempting to evaluate new technologies and/or determine the effects of various policies and technologies. This paper discusses a methodology for measuring the sustainability and economic viability of crop-livestock systems. The approach is based on the concept of intertemporal and interspatial total factor productivity, paying particular attention to the valuation of natural resource stock and flows. The method is applied to a data set available at the International Livestock Centre for Africa. Intertemporal and interspatial total factors productivity indexes are computed for three farming systems in southwestern Nigeria. Results show that the sustainability and economic viability measures are sensitive to changes in the stock and flow of soil nutrients as well as material inputs and outputs. The advantage of this approach is that intertemporal and interspatial total factor productivity measures are computed using only price and quantity data, thus eliminating the need for econometric estimation.